Integrating ESG Principles and Maqāṣid al-Sharī'ah in Islamic Corporate Governance: A Systematic Literature Review - Anggalina Anggalina Fajar Ismianti; Supriyatin (Jurnal Investasi Islam, 2026)
This study aims to map the development of the literature, thematic distribution, and forms of convergence between Environmental, Social, and Governance (ESG) principles and Maqāṣid al-Sharī'ah within the context of Islamic corporate governance, while formulating research gaps and future agendas in a field that remains fragmented. The study employs a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol applied to 585 initial records from Scopus, Web of Science, and Dimensions.ai (2015–2025), which, after a two-stage screening process with excellent inter-rater reliability (Cohen's Kappa = 0.84), yielded 23 selected articles analyzed through a combination of VOSviewer bibliometric analysis and Braun and Clarke's six-phase thematic analysis. The results show a sharply increasing publication trend following the issuance of IFRS S1/S2 in 2023, with the social dimension addressed by all studies (100%), governance by 91.3%, and environmental by 69.6%; however, explicit articulation of specific maqāṣid principles such as ḥifẓ al-bī'ah and amanah remains rare, even though the majority of studies (60.9%) frame the ESG–maqāṣid relationship as complementary a pattern that extends the takaful-sector blueprint findings of Mohd Zain et al. (2024) to a more diverse range of sectors. These findings conclude that the gap in the ESG–Maqāṣid literature lies not in the absence of substantive linkage but in the limited explicit conceptual articulation and empirical testing, and it is therefore recommended that a composite ESG–Maqāṣid index be developed to operationalize amanah and ḥifẓ al-bī'ah in measurable terms, alongside future research expanding into non-financial Islamic corporations and the Gulf region, both of which remain unexplored in this study.